2023
DOI: 10.1177/0958305x221143410
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of soiling effects for east/west vertical bifacial and north/south tilted monofacial photovoltaic farms

Abstract: The output energy produced by the photovoltaic system strongly depends upon the amount of solar radiation harvested by the photovoltaic panels. Varying the tilt of photovoltaic panels at the optimal angle and/or cleaning the photovoltaic panels at regular intervals are some of the techniques that could enhance the photovoltaic system performance albeit at the cost of increased labor and water budget. Here, we explore a farm-level study to investigate the effect of different tilt angle adjustment schedules on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For this reason, it is not easy to determine the optimal inclination angle as it is strongly influenced by the soiling effect and other factors. 91,92…”
Section: Cleaning Techniques Descriptionmentioning
confidence: 99%
“…For this reason, it is not easy to determine the optimal inclination angle as it is strongly influenced by the soiling effect and other factors. 91,92…”
Section: Cleaning Techniques Descriptionmentioning
confidence: 99%
“…For this reason, it is not easy to determine the optimal inclination angle as it is strongly influenced by the soiling effect and other factors. 91,92 Dust deposition and its impact on PV panels were investigated by Jaszczur et al. 93 They demonstrated that successful mitigation of dust from PV surfaces occurs in the case of high-intensity rain, while in the case of low rainfall, it affects PV panels negatively.…”
Section: Natural Cleaning Effect On Pv and Csp Solar Systemsmentioning
confidence: 99%